Influence of pole carriage on sprint mechanical properties during pole vault run-up - Frère, J.; Sanchez, H.; Homo, S.; Rabita, G.; Morin, J.-B.; Cassirame, J. (Computer Methods in Biomechanics and Biomedical Engineering, 2017)
Pole vault performance is highly correlated with the final running velocity of the athlete at take-off (Frère et al. 2010). To achieve top running velocity, the athlete has to develop a large forward acceleration, which is related to the ability to produce and apply a high amount of impulse onto the ground (Rabita et al. 2015). Although it is well known that carrying a pole impairs horizontal velocity output (Gros & Kunkel 1990), only few studies investigated the underlying mechanisms explaining this loss of velocity. For instance, Frère et al. (2009) found in novice athletes a reduction of maximal hip and knee flexion during 30-m sprints with pole carriage that induced a decrease in stride length, and thus, a lower horizontal velocity. However, mechanical changes due to the pole carriage and for a higher level of expertise remain unexplored.